Pengaruh Academic Self-Efficacy terhadap Academic Burnout pada Mahasiswa di Masa Pandemi Covid-19 - Adinda Tiaranissa; Dewi Rosiana (UNISBA Press, 2022)
Abstract. The Covid-19 pandemic has had a wide impact, one of which is in the education field. The presence of the Covid-19 pandemic has made the learning process turn into an online learning method that requires students to study at their homes. This online learning method shows a different impact compare to the learning method carried out before the pandemic. During the pandemic, the online learning process has an impact on student difficulties where students show a decrease in motivation, feel cynical, physically and emotionally exhausted due to the demands of learning with higher intensity during the online learning period. This phenomenon is known as academic burnout. Academic self-efficacy is one of the predictor factors that can affect academic burnout in students. Academic self-efficacy is students' beliefs about their capabilities to complete academic tasks (Zajacova et al., 2005). This study was conducted to see whether there is an influence of academic self-efficacy on academic burnout in Bandung City students during the COVID-19 pandemic. This research is a quantitative study using a causal method followed by 400 respondents from Bandung City students. The measuring instrument in this study used the Academic Self Efficacy Scale from Zajacova et al. (2005), and the Maslach Burnout Inventory-Student survey (MBI – SS) compiled by Schaufeli (2002). The results of this study indicate that there is a significant effect on academic self-efficacy on academic burnout of Bandung City students during the COVID-19 pandemic 10,7% (R2 = 0.107; Sig. 0.00). Abstrak. Pandemi Covid-19 memiliki dampak yang luas secara sosial salah satunya pada ranah Pendidikan. Adanya pandemi Covid-19 membuat proses pembelajaran berubah menjadi pembelajaran daring yang mengharuskan mahasiswa belajar dirumah masing-masing. Selama pandemi, proses pembelajaran yang dilakukan secara daring berdampak terhadap kesulitan mahasiswa dimana mahasiswa menunjukan adanya penurunan motivasi, merasa sinis, kelelahan secara fisik dan emosional dikarenakan oleh tuntutan belajar dengan intensitas yang lebih tinggi di masa pembelajaran daring. Fenomena ini dikenal dengan academic burnout. Academic self-efficacy merupakan salah satu faktor prediktor yang dapat mempengaruhi academic burnout pada mahasiswa. Academic self-efficacy merupakan kepercayaan diri mahasiswa pada kemampuan mereka untuk melaksanakan tugas akademik (Zajacova et al., 2005). Penelitian ini dilakukan bertujuan untuk melihat apakah terdapat pengaruh academic self-efficacy terhadap academic burnout pada mahasiswa Kota Bandung di masa pandemi covid-19. Penelitian ini merupakan penelitian kuantitatif menggunakan metode kausal yang diikuti oleh 400 responden mahasiswa Kota Bandung. Alat ukur pada penelitian ini menggunakan Academic Self Efficacy Scale dari Zajacova et al. (2005), dan Maslach Burnout Inventory- Student survey (MBI – SS) yang disusun oleh Schaufeli (2002). Hasil penelitian ini menunjukan terdapat pengaruh signifikan pada academic self-efficacy terhadap academic burnout mahasiswa Kota Bandung di masa pandemi covid-19 sebesar 10,7% (R2 = 0,107; Sig. 0,00).